2022
DOI: 10.1177/21501319221142426
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Health and Hypertension Control in Adults with Medicaid

Abstract: Background: Social determinants of health (SDOH) are associated with cardiovascular disease, but little is known about mechanisms underlying those relationships. We hypothesized that SDOH would be associated with uncontrolled hypertension (HTN) in adults with Medicaid. Methods: This was a retrospective analysis of adults in a Medicaid accountable care organization who had HTN diagnoses, received regular care at community health centers, and enrolled in a cohort study between December 2019 and December 2020. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In this analysis, we used information extracted from the electronic health record in the Enterprise Data Warehouse to categorize blood pressure control, expanding upon the work from our previous publication (26) where uncontrolled blood pressure was determined via research patient data registry records only. Hypertension was considered uncontrolled if mean systolic blood pressure ≥ 140 mm Hg or mean diastolic blood pressure ≥ 90 mm Hg in the 12 months prior to baseline.…”
Section: Blood Pressurementioning
confidence: 99%
“…In this analysis, we used information extracted from the electronic health record in the Enterprise Data Warehouse to categorize blood pressure control, expanding upon the work from our previous publication (26) where uncontrolled blood pressure was determined via research patient data registry records only. Hypertension was considered uncontrolled if mean systolic blood pressure ≥ 140 mm Hg or mean diastolic blood pressure ≥ 90 mm Hg in the 12 months prior to baseline.…”
Section: Blood Pressurementioning
confidence: 99%
“…Another major category included healthcare utilization metrics like preventable hospital readmissions (n = 11) [136][137][138][139][140][141][142][143][144][145], ED reliance ( n = 16) , and telehealth adoption [169]. Beyond infectious outcomes and healthcare utilization, studies also assessed chronic disease control across conditions like diabetes (n = 11) [170][171][172][173][174][175][176][177][178][179][180], hypertension [173,181,182], kidney disease [183,184], and obesity (n = 7) [146,175,[185][186][187][188][189], along with risk factors like elevated blood pressure and cardiovascular events. Some studies focused on cancer (n = 11) screening, diagnoses, treatment disparities and survival outcomes [167,[190][191][192][193][194][195][196][197][198]…”
Section: Sdoh and Health Outcomesmentioning
confidence: 99%
“…In our review, we identified 164 articles (details see Supplement 168], and telehealth adoption [169]. Beyond infectious outcomes and healthcare utilization, studies also assessed chronic disease control across conditions like diabetes (n = 11) [170][171][172][173][174][175][176][177][178][179][180], hypertension [173,181,182], kidney disease [183,184], and obesity (n = 7) [146,175,[185][186][187][188][189], along with risk factors like elevated blood pressure and cardiovascular events. Some studies focused on cancer (n = 11) screening, diagnoses, treatment disparities and survival outcomes [167,[190][191][192][193][194][195][196][197][198][199], while others addressed mental health (n = 6) indicators [146][147][148][149][150][151] ranging from dementia incidence [200] to suicide (n = 2) risk factors [201,202].…”
Section: Sdoh and Health Outcomesmentioning
confidence: 99%